2018
DOI: 10.1103/physrevb.98.115132
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ultrafast transport on the high-energy states of a photoexcited topological insulator

Abstract: Ultrafast dynamics in three-dimensional topological insulators (TIs) opens new routes for increasing the speed of information transport up to frequencies thousand times faster than in modern electronics. However, up to date, disentangling the exact contributions from bulk and surface transport to the subpicosecond dynamics of these materials remains a difficult challenge. Here, using timeand angle-resolved photoemission, we demonstrate that driving a TI from the bulk-conducting into the bulk-insulating transpo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 71 publications
(102 reference statements)
0
8
0
Order By: Relevance
“…Our results demonstrate that in an intrinsic TI, Bi 2 Te 3 , the picosecond relaxation process is mainly due to surface (resonant) states with strongly limited scattering channels. The complete relaxation occurring at long delays is explained by the energy transfer from the bottom of the TSS to low energy phonons [56][57][58] and electron-hole recombination [30] at the surface (Fig. 4d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results demonstrate that in an intrinsic TI, Bi 2 Te 3 , the picosecond relaxation process is mainly due to surface (resonant) states with strongly limited scattering channels. The complete relaxation occurring at long delays is explained by the energy transfer from the bottom of the TSS to low energy phonons [56][57][58] and electron-hole recombination [30] at the surface (Fig. 4d).…”
Section: Resultsmentioning
confidence: 99%
“…This has motivated out-of-equilibrium experiments on TIs. In particular, time-and angle-resolved photoemission spectroscopy (trARPES) provides valuable information on electron in-teractions [23,[25][26][27][28][29][30] as it gives access to the time evolution of excited carriers in the reciprocal space [31][32][33]. However, detecting the spin degrees of freedom requires a more sophisticated method [18,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, this result highlights the impact of quantization effects on the efficiency of transversal electron transport near E F , which is the main reason for the increasing values of τ l with decreasing thickness. On the other hand, it also provides further evidence for the importance of electronelectron scattering which is, in any case, a slow channel of thermalization due to Auger-like secondary electron emission upon recombination of the hot electron with a hole [41].…”
Section: H Influence Of Quantum Confinement On the Thermalization Timentioning
confidence: 90%
“…There are several effects that can explain this observation. One of them is the influence of ultrafast carrier transport (ballistic or diffusive) [38][39][40][41] from the surface to the bulk of the Au film with increasing thickness. However, the efficiency of these channels should be weak as no Au bulk states are observed in our photoemission spectra.…”
Section: G Transversal Electron Transport As a Benchmarkmentioning
confidence: 99%
“…The performance of these devices depends on the dynamics of the hot carriers in TIs, which can be observed directly by TR-ARPES [4][5][6] . So far, a number of works have been carried on illustrating the recovery process of the excited electrons in TIs due to various mechanisms: such as the phonons assisted, 7,8 the surface states assisted, 9 and the electron-electron scattering assisted. 10,11 Recently, numerous work have reported that the doping with transition metals can introduce novel physical phenomena in TIs, such as quantum anomalous Hall effect (QAHE) 12 , the giant magneto-optical Kerr effect 13 , and chiral Majorana fermions 14 .…”
mentioning
confidence: 99%